Orthodontic camouflage management of a class II malocclusion with excessive overjet- A case report - Sultana, Naznin; Hasan, Md Nazmul; Hassan, Gazi Shamim; Naim, Mir Abu; Akther, Nasrin (Update Dental College Journal, 2014)
In orthodontic practice various treatment modalities have been presented for the treatment for the class II, div 1malocclusions. Recently a large number of young adults have been seeking shorter, cost effective and a non surgical correction of Class II malocclusions and they accept dental camouflage as a treatment option to mask the skeletal discrepancy .This case report presents one such case, a 15years old growing male who has Class II div I malocclusion with sever maxillary incisor proclination, convex profile ,high mandibular plane angle, incompetent lips, increased overjet& overbite, over retained upper left deciduous canine ,impacted upper left canine and a supernumerary tooth in canine region. We considered the camouflage treatment by extracting the upper right first premolar, left impacted canine, deciduous canine and supernumerary tooth. Following the treatment, a satisfactory result was achieved with an ideal, static and a functional occlusion, facial profile, acceptable smile, competent lip and stable treatment results. DOI: http://dx.doi.org/10.3329/updcj.v3i1.17984 Update Dent. Coll. j: 2013; 3 (1): 41-45